2010
DOI: 10.1088/1674-4527/10/9/007
|View full text |Cite
|
Sign up to set email alerts
|

Forecast of the key parameters of the 24-th solar cycle

Abstract: To predict the key parameters of the solar cycle, a new method is proposed based on the empirical law describing the correlation between the maximum height of the preceding solar cycle and the entropy of the forthcoming one. The entropy of the forthcoming cycle may be estimated using this empirical law, if the maximum height of the current cycle is known. The cycle entropy is shown to correlate well with the cycle's maximum height and, as a consequence, the height of the forthcoming maximum can be estimated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Our earlier analysis of the Geneva-Copenhagen survey of FG-type dwarfs (Nordstrem et al, 2004;Holmberg et al, 2007Holmberg et al, , 2009) revealed similar fluctuations with magnitudes substantially exceeding those expected for uniform random (Poisson) space distributions to be present in the solar neighborhood, i.e., in the Galactic field. The fractal nature of the distribution of FG-type dwarfs is believed to also reflect the features of the overall distribution of local stars: we showed (Chumak & Rastorguev, 2015) that the space distribution of FG-type dwarfs in the solar neighborhood differs significantly from uniform random distribution on all available scale lengths (from 1 to 20 pc), i.e., that the stellar medium demonstrates significant and well-defined "coarse-grained structure", which can be described by the average Hausdorff dimension of D ≈ 1.23. One of the main problems in the study of the kinetics of a system of gravitating point masses is the analysis of the forces that act on test particles.…”
Section: Introductionmentioning
confidence: 73%
“…Our earlier analysis of the Geneva-Copenhagen survey of FG-type dwarfs (Nordstrem et al, 2004;Holmberg et al, 2007Holmberg et al, , 2009) revealed similar fluctuations with magnitudes substantially exceeding those expected for uniform random (Poisson) space distributions to be present in the solar neighborhood, i.e., in the Galactic field. The fractal nature of the distribution of FG-type dwarfs is believed to also reflect the features of the overall distribution of local stars: we showed (Chumak & Rastorguev, 2015) that the space distribution of FG-type dwarfs in the solar neighborhood differs significantly from uniform random distribution on all available scale lengths (from 1 to 20 pc), i.e., that the stellar medium demonstrates significant and well-defined "coarse-grained structure", which can be described by the average Hausdorff dimension of D ≈ 1.23. One of the main problems in the study of the kinetics of a system of gravitating point masses is the analysis of the forces that act on test particles.…”
Section: Introductionmentioning
confidence: 73%
“…The amplitudes of solar cycle 24 predicted by researcher are quite dispersed (Obridko and Shelting 2008;Pesnell 2008;Bhatt et al 2009;Ajabshirizadeh 2011;Chumak and Matveychuk 2010;Dabas and Sharma 2010;Du and Wang 2010;Kane 2010;Wang et al, 2002Wang et al, , 2008Wang et al, , 2009). However, a dynamo model tends to predict that the amplitude of solar cycle 24 is about 90 or even at less than 90 (Jiang et al 2007).…”
Section: Summary and Discussionmentioning
confidence: 90%
“…To demonstrate significant differences of the fractal model of gravitating medium from the Poisson model generally adopted in these models numerically estimated for the local solar neighbourhood based on the results of a fractal analysis of the GCS. We adopt D ≈ 1.23 and h ≈ 1.644 for the distribution of conditional density in the fractal medium from our earlier paper (Chumak & Rastorguev, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Scrimgeour et al (2012) also provide an impressive historical review of the problem, to which we refer the interested readers. Chumak & Rastorguev (2015) analysed Geneva-Copenhagen Survey of local FG-type dwarfs (hereafter referred to as GCS) and showed that the space distribution of stars of this type, which represent a significant fraction of the local stellar population, differs significantly from uniform Poisson distribution. We also showed that the distribution of stars on GCS scales is consistent with fractal model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation